Measuring therapeutic relationship in physiotherapy: conceptual foundations. (18th November 2022) - McCabe, Erin; Miciak, Maxi; Roduta Roberts, Mary; Sun, Haowei (Linda); Gross, Douglas P.
ABSTRACT: The "therapeutic relationship" in physiotherapy refers to the beneficial or healing relationship between the patient and physiotherapist. Interest in researching therapeutic relationships in physiotherapy is growing and there is a need for a measure of therapeutic relationship with a strong conceptual foundation. Body of paper: We begin with a general discussion of the state of therapeutic relationship measurement in physiotherapy research – notably, how current research is based on measures borrowed and adapted from psychotherapy. Then, we introduce Miciak's physiotherapy therapeutic relationship framework, discuss why it offers a solid foundation for measurement development, and describe the key concepts in the framework. We then discuss various approaches to measuring therapeutic relationship, illustrating how Miciak's framework could be used to inform their development. We end by discussing current challenges in measuring therapeutic relationship and how these could be addressed.